CYBERBULLYING AS A CRIME - Chyshko , Kateryna (Collection of scientific papers «ΛΌГOΣ», 2023)
Bullying is dangerous not only because of the aggressive actions that accompany this phenomenon, but also because of the special attitude of the bully towards the victim, which is characterized by contempt, disdain, and a persistent feeling of contempt for a specific person. Buhler defines himself as a kind of privileged person, and the presence of imaginary privileges in life becomes his social model of behavior.